Computer system for recording and display of data from newborn infants with respiratory illnesses. Issue 2 (February 1978) - Allen, L P; Clifton, J S; Ingram, D; le Souëf, P N; Reynolds, E O; Wimberley, P D
Abstract : A computer system has been used for the recording and display of data from 277 infants with respiratory illnesses consecutively admitted to a neonatal intensive care unit during a period of 25 months. Improved efficiency of data handling was demonstrated, and the system proved valuable for teaching and research.